Country Partnership Framework for Tunisia for the Period FY 2016-2020 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2016)
This Country Partnership Framework (CPF) for Tunisia, prepared jointly by International Bank for Reconstruction and Development (IBRD), International Finance Corporation (IFC) and Multilateral Investment Guarantee Agency (MIGA) covers the period Fiscal Year (FY) 2016 through FY 2020. The CPF is anchored in the Government of Tunisia’s September 2015 Note d’Orientation Stratégique and the WBG’s October 2015 Strategy for the Middle East and North Africa Region. It builds on extensive discussions with a wide range of stakeholders, and is underpinned by WBG analytics, including the June 2015 Systematic Country Diagnostic (SCD). The Government’s “Note d’Orientation Stratégique” outlines Tunisia’s development vision for the next five years. Its main premise is that Tunisia will maintain its strong partnerships with the international community; rely on the private sector to lead economic growth and job creation; and promote a vibrant civil society. Technical ministries and regions are in the process of preparing their five-year sectorial plans based on this vision, for which financing will be sought during an international donor conference in late 2016.